A novel approach to analyze the association characteristics between post-spliced introns and their corresponding mRNA - Bo, Suling; Sun, Qiuying; Ning, Pengfei; Yuan, Ningping; Weng, Yujie; Liang, Ying; Wang, Huitao; Lu, Zhanyuan; Li, Zhongxian; Zhao, Xiaoqing (Frontiers in Genetics, 2023)
Studies have shown that post-spliced introns promote cell survival when nutrients are scarce, and intron loss/gain can influence many stages of mRNA metabolism. However, few approaches are currently available to study the correlation between intron sequences and their corresponding mature mRNA sequences. Here, based on the results of the modified Smith-Waterman local alignment-based algorithms (SW) and binding free energy weighted local alignment algorithm (BFE), the optimal matched segments between introns and their corresponding mature mRNAs in caenorhabditis elegans and their relative matching frequency (RF) distribution were obtained. The results showed that although the distribution of relative matching frequencies on mRNAs obtained by the BFE method was similar to the SW method, the interaction intensity in 5' and 3' untranslated regions (UTRs) regions was weaker than the SW method. The distributions of matching frequencies in the exon-exon junction regions were comparable and the effects of long and short introns on mRNA and on the five functional sites were similar to the SW method. However, the interaction intensity in 5' and 3'UTR regions with BFE was weaker than with SW. Although the matching rate and length distribution shape of the optimal matched fragment were consistent with the SW method, an increase in length was observed. The matching rates and the length of the optimal matched fragments were mainly in the range of 60-80% and 20-30bp, respectively. Although we found that there were still matching preferences in the 5' and 3' UTR regions of the mRNAs, the matching intensities were significantly lower than the matching intensities between introns and their corresponding mRNAs. Overall, our findings suggest that the interaction between introns and mRNAs results from synergism among different types of sequences during the evolutionary process.